2021
DOI: 10.1038/s41591-021-01408-4
|View full text |Cite
|
Sign up to set email alerts
|

First-dose ChAdOx1 and BNT162b2 COVID-19 vaccines and thrombocytopenic, thromboembolic and hemorrhagic events in Scotland

Abstract: Reports of ChAdOx1 vaccine–associated thrombocytopenia and vascular adverse events have led to some countries restricting its use. Using a national prospective cohort, we estimated associations between exposure to first-dose ChAdOx1 or BNT162b2 vaccination and hematological and vascular adverse events using a nested incident-matched case-control study and a confirmatory self-controlled case series (SCCS) analysis. An association was found between ChAdOx1 vaccination and idiopathic thrombocytopenic purpura (ITP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
265
8
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(295 citation statements)
references
References 30 publications
18
265
8
4
Order By: Relevance
“…They found that there was an excess (observedexpected) of 1.33 cases of non-immune thrombocytopenia per 100,000 people and 0.45 per 100,000 for immune thrombocytopenia. There was also evidence of a small increase in arterial thrombosis and haemorrhagic events but no increase in venous thromboembolic events (Simpson et al, 2021). Thus, it would appear that platelet activation in response to AZD1222 is a real but rare (around 1 in 100,000) event although it is not clear if this is due to a response to the Adenovirus vector or to the SARS-CoV-2 spike protein or even to a combination of the two.…”
Section: Vaccine-related Thrombosismentioning
confidence: 96%
“…They found that there was an excess (observedexpected) of 1.33 cases of non-immune thrombocytopenia per 100,000 people and 0.45 per 100,000 for immune thrombocytopenia. There was also evidence of a small increase in arterial thrombosis and haemorrhagic events but no increase in venous thromboembolic events (Simpson et al, 2021). Thus, it would appear that platelet activation in response to AZD1222 is a real but rare (around 1 in 100,000) event although it is not clear if this is due to a response to the Adenovirus vector or to the SARS-CoV-2 spike protein or even to a combination of the two.…”
Section: Vaccine-related Thrombosismentioning
confidence: 96%
“…Estimating the 'true effect' is hampered by the multiple challenges associated with the diagnosis of ITP and the low number of incident ITP events observed. Overall, the authors conclude there is no clear evidence of an association of ITP with the first dose of the BNT162b2 vaccine and there is a possible small increased risk of ITP with the ChAdOx1 vaccine 1 .…”
mentioning
confidence: 90%
“…With all of its benefits, there also comes the potential for side effects, including autoimmune responses. In this issue of Nature Medicine, Simpson and colleagues implicate the AstraZeneca (ChAdOx1) vaccine, but not the Pfizer (BNT162b2) vaccine, in the development of immune thrombocytopenia (ITP) 1 . In interpreting such findings, it is important to consider not only the strengths and limitations of the study but also the wider clinical context and the balance of risks and benefits of vaccination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The autoimmune bleeding disorder is characterised by a decrease in the number of platelets, which can cause minor bruising in some patients and excessive bleeding and long term illness in others. The authors of the study, published in Nature Medicine , stress that the condition is treatable and that the benefits of vaccination greatly outweigh the risks 1…”
mentioning
confidence: 99%